Knowledge Hiding in Small Medium Enterprise Owned by Family Business: The Role of Knowledge Complexity, Psychological Ownership and Avoidance Motivation - Widjaja, William; Wijayadne, Devi Rahnjen (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
This study aims to formulate and answer phenomena related to the competitiveness of family business-based SMEs in the era of disruption from the perspective of knowledge hiding bevahior (KHB), which is influenced by knowledge complexity (KC), psychological ownership (PO) and moderated by avoidance motivation. This research is a survey research type with a quantitative approach. The analytical technique used is SEM-PLS with the help of analysis tools using SMART-PLS 3.0. In addition, simple slope analysis is used to see the moderating role of avoidance motivation in moderating the effect of psychological ownership on knowledge hiding. Respondents in this study were 187-line managers from 78 SMEs. The sampling technique used was non-probability sampling with a saturated sampling method. The results showed that all hypotheses were accepted, which means that psychological ownership has a positive and significant effect on knowledge sharing, and avoidance motivation can moderate psychological ownership on knowledge sharing. This study contributes to examine the source and effect KHB, thereby providing a method for SMEs, particularly in Indonesia, to effectively reduce KHB. This study also finds AM as a moderating variable that modulates the effect of KC on KH, whereas this was rarely explored in earlier study.